2004
DOI: 10.1038/sj.bjc.6602082
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of radiological-guided insertion of implanted central venous access port devices (CVAPD) for the delivery of chemotherapy in cancer patients: institutional experience and review of the literature

Abstract: Central venous access port devices (CVAPD) are necessary for delivery of prolonged infusional chemotherapy or in patients with poor peripheral venous access. Previous studies of Hickman catheters report complication rates in about 45% of patients. Our aim was to assess the early and late complication rate, and duration that the CVAPD remained functional, following insertion by interventional radiologists in patients with solid tumours. A prospective study was undertaken in 110 consecutive patients who had inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 27 publications
(20 reference statements)
7
52
0
5
Order By: Relevance
“…As in other studies, [7,9,11,13,14] the main complication observed in our study was infection, occurring in 5.3% of patients and accounting for half the total number of premature device removals.…”
Section: Incidence Of Complicationssupporting
confidence: 85%
See 1 more Smart Citation
“…As in other studies, [7,9,11,13,14] the main complication observed in our study was infection, occurring in 5.3% of patients and accounting for half the total number of premature device removals.…”
Section: Incidence Of Complicationssupporting
confidence: 85%
“…Cancer patients have an intrinsically high risk of venous thrombosis, related to both the disease process itself and certain cancer treatments, [8] this risk being further increased by placement of a catheter or TIVAPS. [1] Several studies in cancer patients have investigated potential risk factors for TIVAPS-related complications, including the vein accessed [5,9,10] and patient age and gender [11,12], with somewhat conflicting results. Yildizeli analysis of paediatric patients, showed a higher risk of infection after TIVAPS implantation in younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Landmark-mark based punctures of the subclavian vein in particular were associated with increased rates of pneumothorax (11,(13)(14)(15)(16)(17). In addition, infection rates were lower for ultrasound-guided approaches with the Seldinger technique (1.1-8.8%) (3,11,13,18,19) compared with surgical cut-down (0.8-16.3%) (10,(20)(21)(22)(23)(24)(25). Moreover, the radiological technique does not require general anesthesia and is cost effective (26).…”
mentioning
confidence: 99%
“…The option of using the IVAD already in place must be considered as it is easier for the patients, especially for children in whom this IVAD can further be used for administering high-dose treatments and PBSC rescue. 7 Finally, the use of previously implanted IVAD might provide a significant advantage both in terms of patient quality of life and cost savings and should thus be discussed in this setting. This retrospective study provides a sound basis for a future prospective work addressing the question of the use of larger devices (high-resistance totally implantable VA port systems) allowing the use of higher pressure, which should soon become available in our institution.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] There is no literature addressing the feasibility of apheresis using this type of central venous device. In most French centers, a second central or peripheral venous catheter is usually required for apheresis procedures.…”
Section: Introductionmentioning
confidence: 99%